Knowledge and attitude on biostatistics in medical curriculum among medical students - ., Bharti; Kumar, Abhishek; Singh, Abhay; D., Vinoth Gnana Chellaiyan; Singh, Neetu; Dixit, Shivam (International Journal Of Community Medicine And Public Health, 2021)
Background: Medical biostatistics has got an important role in the modern medical science curriculum. The present study was planned to assess the knowledge and attitude among medical graduates regarding the role and utility of biostatistics in medical science. Methods: A cross-sectional study among 120 medical students of MBBS final professional of Saraswati Medical College, Lucknow was conducted by using a pre-designed, pre-tested and semi-structured questionnaire. A Chi-square test was applied to find a statistical association. A p value of <0.05 is considered to be significant. Results: Most of the students considered biostatistics is important and helps them in their UG/PG curriculum and thesis/dissertation. Fifty-seven per cent of the study participants are aware of any software used in the analysis of data. Males used at least anyone statistical software more than females (p=0.017). The majority of males (70.3%) and females (67.4%) expressed that it is difficult to understand the concepts of biostatistics. Almost all males (97.30%) and majority females (84.80%) reported that biostatistics textbooks need to be written in simple language (p value=0.026). Conclusions: The role of biostatistics among medical students is of utmost importance as research purpose and importance is increasing in all domains of medical sciences, moreover, the basics of biostatistics should play a pivotal role in the current medical curriculum.